Réponses

2013-09-14T19:10:06+02:00
Bonjour, je peux t'aider pour la dernière question.
E =  \frac{1}{3}+ \frac{2}{21}- \frac{5}{7}
= \frac{7}{21}+ \frac{2}{21}- \frac{5}{7}
= \frac{9}{21}- \frac{5}{7}
= \frac{9}{21}- \frac{15}{21}
= -\frac{6}{21}
=- \frac{2}{7} <== SIMPLIFIER

F =  \frac{5}{8}- \frac{3}{4}* \frac{16}{9}
= \frac{5}{8}- \frac{48}{36}
= \frac{45}{72}- \frac{96}{72}
=- \frac{17}{24} <== SIMPLIFIER

G =  \frac{45}{28}: (-\frac{15}{7})
= \frac{45}{28}* (-\frac{7}{15})
= -\frac{3}{4} <== SIMPLIFIER